2022
DOI: 10.1128/aac.00793-22
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Pharmacodynamic Characterization of Resistance versus Heteroresistance of Colistin in E. coli Using a Semimechanistic Modeling of Killing Curves

Abstract: Heteroresistance corresponds to the presence, in a bacterial isolate, of an initial small subpopulation of bacteria characterized by a significant reduction in their sensitivity to a given antibiotic. Mechanisms of heteroresistance versus resistance are poorly understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…In terms of parameters, the finding that EC 50 but not E max could be shared between susceptible and resistant subpopulations for CST is consistent with an earlier observation that heteroresistant bacteria differed from the corresponding dominant populations by E max only, i.e. there was no difference in their EC 50 34 . That EC 50 could be a shared parameter for the four different strains is in line with their similar MIC CST values (0.5–0.75 mg/L).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In terms of parameters, the finding that EC 50 but not E max could be shared between susceptible and resistant subpopulations for CST is consistent with an earlier observation that heteroresistant bacteria differed from the corresponding dominant populations by E max only, i.e. there was no difference in their EC 50 34 . That EC 50 could be a shared parameter for the four different strains is in line with their similar MIC CST values (0.5–0.75 mg/L).…”
Section: Discussionsupporting
confidence: 89%
“…Mechanistically, both heteroresistance and adaptive resistance may however occur for CST. The concurrent presence of these two phenotypic traits in the same strain has earlier been suggested 28,29 , and both model structures have been successfully applied to describe polymyxin effects without a clear pathogen-dependent preference [30][31][32][33][34] . In terms of parameters, the finding that EC 50 but not E max could be shared between susceptible and resistant subpopulations for CST is consistent with an earlier observation that heteroresistant bacteria differed from the corresponding dominant populations by E max only, www.nature.com/scientificreports/ i.e.…”
Section: Discussionmentioning
confidence: 99%
“…As the strain displayed decline in cell counts due to colistin treatment in the time kill assay (Figure 5), which was resembling trend reported earlier for colistin heteroresistant bacteria [46], we evaluated whether the MDR clinical isolate of E. coli U1007 displays colistin heteroresistance by performing population analysis profile as reported earlier [47]. U1007 strain was serially diluted and spotted on plates containing increasing concentrations of colistin and cell counts were compared with strain plated on antibiotic free plates and if the ratio greater than 0.0001 the tested strain is deemed as colistin heteroresistant.…”
Section: Time Kill Studysupporting
confidence: 86%
“…Thus, we concluded that the initial population (starting inoculum) consisted of two subpopulations, representing a heterogenous bacterial population with a proportion (F1) of bacteria being a highly susceptible dominant population (S1) and the remaining sub-dominant population (S2) having a lower susceptibility. F1 was estimated by the model illustrated in Figure 2 and as shown by Mead et al [11].…”
Section: Pre-existing Heterogenous Population Modelmentioning
confidence: 99%
“…Models describe (1) bacterial growth and natural death, (2) drug effects, (3) regrowth and resistance emergence, and (4) antibiotic combinations and their interactions [8]. These models have been implemented in veterinary medicine [7,11,12]. With regard to veterinary fluoroquinolones (FQs) and canine skin pathogens, different studies have evaluated their killing effects in comparison with other antimicrobial classes using standard kill curves without modelling [13,14] or a simple inhibitory I max model using only the final bacterial counts at 24 h [15].…”
Section: Introductionmentioning
confidence: 99%